Ampicillin Induced Oral Candidiasis: A Case Report - Panachiyil, George Mathew; Babu, Tirin; Sebastian, Juny; Ravi, Mandyam Dhati (Indian Journal of Pharmacy Practice)
A six year old boy presented to the outpatient department of the hospital with complaints of dysphagia since 2 days. He was previously treated for nephrotic syndrome with hypertension and was on tablet prednisolone (40mg, once daily). From eight days prior to hospital admission, he was on injection ampicillin (500mg, three times daily) for respiratory tract infections. He was diagnosed as having oral candidiasis induced by the use of ampicillin. The oral candidiasis was managed with topical application of clotrimazole (1%) 3-4 times daily following the withdrawal of ampicillin. The following case presents an evidence that ampicillin in therapeutic dose can be associated with oral thrush.
Keywords: Ampicillin; Aminopenicillin; Oral Candidiasis; Thrush; Case Report.